Organizational Emplacement as a Response to Digital Threat: The Novel Resurgence of Independent Bookstores - Raffaelli, Ryan; Noe, Ryann (Administrative Science Quarterly, 2025)
This study reveals how incumbent actors leverage physical place as a source of differentiation in response to the threat of digital commoditization. Through a longitudinal, qualitative analysis of the U.S. independent bookselling industry from 1995 to 2019, we outline how dispersed organizational actors responded to the rise of Amazon.com, an online retailer that threatened to displace brick-and-mortar retail. While many analysts predicted that Amazon’s emergence would incite a retail apocalypse, independent bookstores proved to be far more resilient than expected. We identify organizational emplacement—a process by which actors infuse meaning into physical spaces , thereby transforming them into valuable places —as a novel mechanism of value creation. Several practices are associated with this mechanism, including architecting the physical environment, anchoring to the local community, and sanctifying the meaning of place. This study offers a counterbalance to narratives of digital displacement and shows how physical place can be converted from a liability into an asset in the digital era.